(untitled) (International Journal of Ayurveda and Pharma Research, 2017)
India is endowed with a rich wealth of medicinal plants which have been a valuable source of natural products for maintaining human health. A large number of these medicinal plants are used in various formulations for the treatment of several disease caused by microbes. Medicinal plants constitute an effective source of traditional and modern medicines. Ayurveda a system of Indian traditional form of alternative medicines. A major aspect of conservation of medicinal plants is their considerable economic and social value. Natural source of medicinal plants are often unable to meet demand for popular herbal products. Populations of many species have limited distribution in their natural habitats, led to genuine or arbitrary substitution by other plants. Unavailability of such medicinal plants has led to arbitrary substitution and adulteration in the raw drug market. Aromatic plants are prime economic importance because of the continuous increased demands for their products by local foreign markets. At present the adulteration and substitution of herbal drugs is the burning problem in herbal industry and it has caused a major advancement in the research on commercial natural products. The article throws light on preliminary pharmocognostic and phytochemical investigation of one pair of Abhava Pratinidhi Dravya viz. Tulasi and Nirgundi.